EVALUATION OF DYNAMIC BALANCE IN KNEE OSTEOARTHRITIS PATIENTS WITH SIGNIFICANT VARUS DEFORMITY - Ece Aydoğ; Duygu Yazar; Ajda Bal; Emel Ekşioğlu; Ece Ünlü; Aytül Çakçı (Archives of Rheumatology, 2005)
Objective: The aim of this study was to investigate dynamic balance in bilateral knee osteoarthritis (KO) patients with varus deformity in relation to the functional disability. Methods: Fifty-eight patients (54 women and 4 men) with KO with significant varus deformity and thirty-five (31 women and 4 men) controls of same age, gender,weigth, heigth and body mass index group were tested using Biodex Stability System (Biodex medical systems, Shirley, NY). Anterior / Posterior Index (AP), Medial / Lateral Index (ML) and Overall Index (OA) were obtained with bilateral stance at a platform stability of 8. Subjects were tested with "eyes open" all times. Lequesne index was used for the assessment of disability in the patients with knee OA. Results: Overall, Anterior/Posterior, and Medial/Lateral indices in KO group were significantly higher than control group. For OA index, the results were 4.02 ± 1.48 in KO, 3.12± 1.42 in the control group (p:0.001). For AP index, the results were 3.01 ± 1.09 in KO, 2.52 ± 1.24 in the control group (p:0.012). For ML index, the results were 2.76± 1.27 in KO and 2.09 ± 1.10 in the control group (p: 0.003). Statistically significant correlation was found between Lequesne pain score and ML stability index (r:0.266 p:0.042). A similar correlation was determined between Lequesne daily living activities score and OA and AP stability indices ( respectively; r:0.276 p:0.033; r:0.305 p:0.18). However, a positive correlation was not detected between total Lequesne index score and postural balance for all of three stability indices. Conclusion: KO with significant varus deformity has negative effect on the postural stability. Results suggest the importance of balance training in this population.